Challenges to Higher Education in Laos and Cambodia - Hayden, Martin (International Higher Education, 2019)
The higher education systems in Laos and Cambodia have been expanding rapidly over recent years, but with increasing reliance on a teaching-only private higher education sector, the quality of which is extremely variable. Public-sector higher education institutions, though generally considered more prestigious to attend, are severely constrained by a lack of institutional autonomy and limited budgets, and so their quality is also a matter for concern.